Volume 3: Materials Technology; Jan Vugts Symposium on Design Methodology of Offshore Structures; Jo Pinkster Symposium on Seco 2011
DOI: 10.1115/omae2011-49169
|View full text |Cite
|
Sign up to set email alerts
|

On the Structural Capacity of Grouted Connections in Offshore Structures

Abstract: During the last year, the offshore wind tower structure industry experienced that the design of the grouted connections between the top tower and monopile structure did not necessarily result in an acceptable safety level. A number of wind towers were reported to settle on the monopile structure and the resulting force flow in the structures was different to that intended at the design stage. A joint industry project was therefore carried out to investigate the structural capacity of these connections. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In contrast, the SHS column connection can be applied in modular construction industry as it is easy for installation, arrangement and standardization. Extensive studies have been conducted to investigate failure modes and load resistances of CHS pile-to-sleeve connections [20][21][22]. Axial load resistance of a grouted connection is attributed to the bond strength due to friction and adhesion between grout and steel tube, and the mechanical interlock provided by shear keys [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the SHS column connection can be applied in modular construction industry as it is easy for installation, arrangement and standardization. Extensive studies have been conducted to investigate failure modes and load resistances of CHS pile-to-sleeve connections [20][21][22]. Axial load resistance of a grouted connection is attributed to the bond strength due to friction and adhesion between grout and steel tube, and the mechanical interlock provided by shear keys [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In order to get more accurate calculation methods, further studies have been conducted. In combination with practical engineering, Lotsberg et al [11] revealed that the axial bearing performance of a grouted connection was much more affected by the diameter and surface manufacturing error of the connection segment than that described in the specification. Dallyn et al [12] obtained the correlation of these parameters through a great deal of parameter analysis and provided suggestions for ensuring the design reliability of bearing performance.…”
Section: Introductionmentioning
confidence: 99%